2017
DOI: 10.3390/su9060878
|View full text |Cite
|
Sign up to set email alerts
|

Sea Reclamation Status of Countries around the South China Sea from 1975 to 2010

Abstract: Abstract:As a way of turning sea into land for living space for humans, the actions of sea reclamation bring about significant benefits. Nevertheless, it is also an under-recognized threat to the environment and the marine ecosystem. Based on images in two periods, sea reclamation information of countries around the South China Sea was extracted from 1975 to 2010. The spatial state and driven forces of sea reclamation are then discussed. Results show that the overall strength of sea reclamation in the South Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…First, we found that land use in the coastal areas of Vietnam showed a trend of continuous and rapid increase in construction land and had observable spatial variation characteristics. This observation was comparable to the existing research on hot spots with rapid development [67][68][69][70]. Specifically, the research results of this study are similar to these of other regions in Vietnam, other countries in Southeast Asia, the South China Sea, and Asia.…”
Section: Discussionsupporting
confidence: 90%
“…First, we found that land use in the coastal areas of Vietnam showed a trend of continuous and rapid increase in construction land and had observable spatial variation characteristics. This observation was comparable to the existing research on hot spots with rapid development [67][68][69][70]. Specifically, the research results of this study are similar to these of other regions in Vietnam, other countries in Southeast Asia, the South China Sea, and Asia.…”
Section: Discussionsupporting
confidence: 90%
“…Pulau Ujong (Singapore) has undergone significant urban works in the last five decades, including coastal reclamation (Yong et al, 1991; Zhang et al, 2017). In particular, both the Tuas industrial area and the eastward extension of the Changi airport were constructed with progradation rates of about 290 m per year (National University of Singapore Libraries, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Martin-Anton et al 2016 [170] assessed the world's land reclamation situation using Google Earth and showed that the highest development exists in East Asian countries (China, Japan, and Korea). Zhang et al, 2017 [171] focused especially on the South China Sea, using SRS from Landsat to assess the situation between 1975 and 2010. Pressures from land reclamation activities lead to environmental change and degradation of coastal natural habitats, such as wetlands and dunes.…”
Section: Land Reclamationmentioning
confidence: 99%